Seton Hall University doctor of science degree program: clinical doctorate in audiology. - Koehnke J; Besing J; Shea-Miller K; Martin B (American Journal of Audiology, 2004)
This article provides an overview of the clinical doctoral program in audiology at Seton Hall University. It is a full-time, 4-year program that includes academic course work, clinical practica, and research experience. In concert with the university mission, the program is designed to enable students to develop the skills they need to be leaders in the field of audiology, providing assessment and intervention to individuals with hearing problems and enhancing the knowledge base of the profession. As part of the School of Graduate Medical Education, students in the program have access to a wealth of resources in related health professions. The close proximity to New York City provides many opportunities for outstanding clinical education with a diverse population.